2012
DOI: 10.1016/j.ajpath.2012.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Damage in Fetal and Newborn Cystic Fibrosis Pigs Involves the Activation of Inflammatory and Remodeling Pathways

Abstract: Pancreatic disease has onset in utero in humans with cystic fibrosis (CF), and progresses over time to complete destruction of the organ. The exact mechanisms leading to pancreatic damage in CF are incompletely understood. Inflammatory cells are present in the pancreas of newborn pigs with CF (CF pigs) and humans, which suggests that inflammation may have a role in the destructive process. We wondered whether tissue inflammation and genes associated with inflammatory pathways were increased in the pancreas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…CF pigs have multisystem disease that recapitulates the human disease and exhibit a severe pancreatic phenotype. The pancreatic lesions start in utero and progress over time in this model [39], in concordance with the previous autopsy studies of humans with CF [40]. The newborn CF pig pancreas has acinar cell loss, duct proliferation, dilated acini/ducts with zymogen-like material, expansion of interlobular connective tissue, and scattered inflammatory cell aggregates [38,39].…”
Section: Pancreatic Damage In Cf a Experimental Observations In supporting
confidence: 71%
See 1 more Smart Citation
“…CF pigs have multisystem disease that recapitulates the human disease and exhibit a severe pancreatic phenotype. The pancreatic lesions start in utero and progress over time in this model [39], in concordance with the previous autopsy studies of humans with CF [40]. The newborn CF pig pancreas has acinar cell loss, duct proliferation, dilated acini/ducts with zymogen-like material, expansion of interlobular connective tissue, and scattered inflammatory cell aggregates [38,39].…”
Section: Pancreatic Damage In Cf a Experimental Observations In supporting
confidence: 71%
“…As in humans [42], the pancreatic fluid is acidic, low in volume and high in protein and concentrated in CF pigs at birth [43]. The proinflammatory, complement cascade, proapoptotic, and profibrotic pathways are activated in CF pig pancreas, and likely contribute to the destructive process [39].Hegyi et al Page 6Rev Physiol Biochem Pharmacol. Author manuscript; available in PMC 2017 January 12.…”
mentioning
confidence: 99%
“…As in humans [7, 22, 34–36, 4346], the exocrine pancreatic damage starts in utero in CF pigs [33] and progresses over time [29]. We have previously demonstrated that fetal CF pig pancreata (83–90 day, pig gestation is ~114 days) have patchy loss of zymogen-filled acini, inflammation and tissue destruction and these lesions progress into the newborn period [33].…”
Section: Resultsmentioning
confidence: 99%
“…At birth, CF pig pancreata have reduced number of acini, decreased cytoplasmic zymogen granules, and ectatic and plugged ducts surrounded by degenerative exocrine tissue. Over time, the exocrine pancreas is replaced by fat and fibrous tissue [2933], as it occurs in humans with CF [8, 34–36]. With multi-organ disease and exocrine pancreatic disease that is similar to human disease, the CF pig model offers a unique opportunity to investigate the pathogenesis of CFRD.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory damage to the pancreas of CFTR knockout pigs begins in utero on embryonic day 83 (pigs have a 114-day gestation) and 100% of CF pigs have EPD at birth. 95,96 By contrast, newborn CFTR knockout ferrets exhibit relatively mild histopathology of the exocrine pancreas characterized by ADD similar to that seen in CF infants. 90,97 Interestingly, a small subset of CFTR knockout ferrets (<1%) demonstrates pancreatic sufficiency throughout life with normal weight gain and only minor exocrine damage.…”
Section: Pancreatic Diseasementioning
confidence: 99%